Fallow Weed Control with Postemergence Applications of AGH15004, AG14039, Roundup PowerMax, and Atrazine - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
All treatments except AGH15004 at 1.5 pt/a plus Roundup PowerMax (glyphosate) and nonionic surfactant provided more than 95% kochia control at 14 days after treatment (DAT). By 28 DAT, only those treatments containing atrazine provided greater than 95% kochia control. However, kochia control at 42 DAT was greater than 90% with all treatments except Roundup PowerMax plus nonionic surfactant.
Keywords: fallow weed control; postemergence applications; kochia; Russian thistle; AGH15004; Fluroxypr; 2; 4-D; AG14039; Atrazine; Roundup PowerMax; Glyphosate; Kochiavore; Bromoxyn